EFEKTIFITAS LATIHAN REFLEKSI KAKI DENGAN MENGGUNAKAN TEMPURUNG KELAPA TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI PRIMER - Febri Nazwarul Fauzan; Bayhakki ' '; Arneliwati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Hypertension is a degenerative disease that has the highest mortality rate. The purpose of the research was to analize the effect of foot reflexology exercise using coconut shells on blood pressure in patients with primary hypertension. The research used quasy experimental design with non-equivalent control group which divided into experimental group and control group. Sample of this research was 30 respondents divided into 15 respondents as experimental group and 15 respondents as control group. Sample in this research taken using purposive sampling. The equipment was used to measure blood pressure was sphygmomanometer. Data then analyzed into univariate analysis and bivariate analysis using Wilcoxon test and Mann-Whitney test. The result of the research showed that mean of the average systolic and diastolic blood pressure before given foot reflexology training was 156.00 mmHg and 96.67 mmHg. Mean of the average systolic and diastolic blood pressure after a given foot reflexology training was 135.33 mmHg and 79.33 mmHg while systolic p value= 0,000 and diastolic p value = 0,001 (<0,05), it meant blood pressure decreased significantly after intervention given.Foot reflexology using coconut shells can reduce blood pressure for patients with primary hypertension. It is expected to be one of the nursing intervention to reduce blood pressure for patients with primary hypertension. Keywords: blood pressure, coconut shells, foot reflexology exercise, hypertension.